Bias Kognitif, Etika Profesi dan Keputusan Pelaporan Keuangan Dimoderasi Literasi Keuangan - Herbowo; Erdi, Tio Waskito (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Abstrak— This study aims to analyze the effect of cognitive bias and professional ethics on financial reporting decisions, with financial literacy as a moderating variable. The phenomenon of inaccurate reporting and information manipulation indicates that financial reporting decisions are influenced not only by technical aspects but also by behavioral and moral factors. This research applies the Behavioral Decision Theory and the Ethical Decision-Making Model using a quantitative explanatory approach. The data were analyzed using PLS-SEM with SmartPLS 4, involving 116 respondents consisting of accountants, auditors, and financial staff. The results show that cognitive bias has no significant effect on financial reporting decisions, while professional ethics has a positive and significant influence. Furthermore, financial literacy does not moderate the relationship between cognitive bias and financial reporting decisions, nor between professional ethics and financial reporting decisions. The R-Square value of 0.593 indicates that 59.3% of the variance in financial reporting decisions is explained by the studied variables. These findings emphasize that the quality of financial reporting is determined more by moral integrity and professional ethics than by cognitive ability or financial literacy. Therefore, strengthening ethical values and fostering an organizational culture of integrity are essential to improving transparency and accuracy in financial reporting.